Synthesis of some derivatives of 1-aryltetrazol. - Lý, Hoàng Thị; Triệu, Nguyễn Đình (Vietnam Journal of Chemistry, 2012)
Some derivatives of 1-aryltetrazol were synthesized by the interation of hydroacid and naphtylamines in present of triethylorthofomiate. The structures of products were indentified by UV, IR, MS , 1H.NMR and HMBC-HSQC spectra.